Rhino-Orbital-Cerebral Mucormycosis: An Uncommon Cause of Stroke in Young Adults - Mello Vieira, Marta; Salvado de Morais, Mariana; Barbosa, Sara; Cunha, Sofia; Monteiro, Manuel; Soares, Leonor; Fevereiro, Maria do Carmo (International Journal of Innovative Research in Medical Science, 2025)
Rhino-orbital-cerebral mucormycosis is an invasive fungal infection that primarily affects immunocompromised individuals, particularly those with haematological malignancies, organ transplant recipients, and uncontrolled diabetes. Following initial infection of the nose and sinuses, fungal vascular invasion and bone erosion can lead to the spread of the disease to adjacent tissues, notably the orbits and brain, with the potential for multiple cerebrovascular complications. Early diagnosis and prompt treatment initiation are crucial for effective disease control. We report the case of a 29-year-old woman with a history of long-term uncontrolled type 1 diabetes, who was diagnosed with mucormycosis. Despite the absence of neurological symptoms initially, both computed tomography and magnetic resonance imaging revealed ischaemic lesions in the left cortico-subcortical occipital, parietal, and frontal regions, caused by occlusion of the left cavernous internal carotid artery and left anterior cerebral artery. The patient later developed diplopia and underwent surgical intervention, prolonged antifungal therapy, and hyperbaric oxygen therapy, resulting in a slow but positive recovery. This rare case of stroke in a young adult underscores the importance of excluding cerebrovascular complications in rhino-orbital-cerebral mucormycosis, even in the absence of neurological symptoms, to prevent further damage and morbidity.